African Solutions to African Problems: The most recent chapter in the war diary of Eeben Barlow. - Pongrácz, Bálint (Journal of Central and Eastern European African Studies, 2025)
Eeben Barlow's third book, "The War for Africa, Conflict, Crime, Corruption & Foreign Interest" gives a personal, often witty yet indisputably forthright insight into the secretive world of private military contractors in Africa. Incorporating a number of venturous endeavours in no less than ten countries of the continent, it is an accessible and entertaining read for the general public. Additionally, for academics and policymakers, the book provides a unique local perspective on the contemporary African security environment.